Multiphase flow correlations (Part 1): Development and applications - Ismail, Issham (Faculty of Chemical & Natural Resources Engineering, 1992)
In the petroleum industry, multiphase flow correlations were developed in order to generate pressure traverse data along the production string and wellbore, to select correct tubing sizes for new production and infill wells, and also to design artificial lift installation at some later date. A simulation program is normally required to perform those tasks due to the repetitive step like nature of the calculation of the multiphase flow correlations.